(untitled) (Update Dental College Journal, 2021)
Objective: To determine the prevalence of malocclusion in school-age children from a selective area of the urban and rural community of Bangladesh. Methods: A cross-sectional descriptive survey was conducted among 748 children aged 08-12 years old were examined from October 2019 to September 2020 in Sylhet Sardar Upazila, Bangladesh. Angle”s classification was used for recording molar relationship with malocclusion traits. The study participants were examined by disposable dental tools (calibrated probs and mirror) including torchlight. After the collection of all data, it was compiled and analyzed by Statistical Package for the Social Sciences (SPSS) Windows version 23. Chi-square test was used for categorical variables. P values <0.05 were considered as statistically significant. Result: The prevalence of malocclusion in urban school-age children was 237(63.4%) and in rural 213(57.0%).In urban area, the prevalence of malocclusion was 109(58.3%) in boys and 128(68.4%) in girls group. The majority (70.5%) were found Angle’s class I in urban group and 148(69.5%) in rural. One forty three (60.3%) patients were found increased overbite with malocclusion in urban group and 124(58.2%) in rural. Angle’s class-I malocclusion and Increased overbite were the most commonly occurring malocclusion. Conclusion: Prevalence of malocclusion was more in urban school age children when compared with rural. Malocclusion was significantly more in girls than boys in both urban and rural area. Angle’s class-I malocclusion and Increased overbite were the most commonly occurring malocclusion of school age children from a selected urban and rural community of Bangladesh. Update Dent. Coll. j: 2021; 11(2): 10-15